Making decisions in emergency surgery. Issue 6 (8th May 2013) - Campbell, Graeme; Watters, David A. K.
Abstract Background Good decision making is essential in surgery. In an emergency, the time for decision making is often short, and the information available is incomplete. The way experienced surgeons make decisions is often not well understood, and therefore is difficult to teach to trainees. Methods This paper examines how decisions are made, based on recent literature and the experience of the authors and their colleagues. Discussion An accurate assessment precedes decision making, and is directed towards the patient, the personnel and environment. Studies of other high‐stakes professions have highlighted the existence of two distinct mental processing symptoms. One is fast and frugal, relying on pattern recognition or following a rule or protocol. This is often performed at a subconscious level. The other is a conscious, reasoned, analytical process. This requires adequate, available mental capacity. In reality, expert and experienced decision makers can adopt either or both approaches, and match their approach to the situation. Decisions made need to be constantly reviewed, particularly where there is mismatch between what was anticipated and what is encountered. Conclusion An algorithm of decision making in emergency surgery has been developed that is based on assessment, the decision required and the outcome of the decision. The decision must also consider the urgency of the situation and the likely outcome if the plan made fails.